Significados y efectos del voluntariado en los Juegos Panamericanos y Parapanamericanos Lima 2019 y el Proyecto Especial Legado - Cueto, Rosa María (2024)
This study analyzes through a qualitative study of 4 focus groups (n=13) the meanings and effects of volunteering reported by volunteers of the Lima 2019 Pan American and Parapan American Games and the Special Legacy Project. On a personal level, positive emotions are reported, linked to the awareness of having been part of historic events, as well as experiences of personal and interpersonal growth. From the social point of view, favorable effects are reported for the construction of a sense of community, civic awareness and national pride. In the institutional framework, organizational and management aspects are identified that favor favorable conditions for the development of volunteer experiences that generate positive effects both personally and socially.